A imagem na educação budista indo-tibetana - Confortin, Daniel (2016)
Indian culture is one of the main matrices of human knowledge. The management of its diversity is a laboratory, a fertile field for research, in the various areas of academic knowledge. Born within this cultural context Buddhism was the first universal religion to be known in history, and over the last few millennia, the majority of the world's population lived under its direct or indirect influence. This research proposes to study a peculiarity of Himalayan Buddhism: the emergence and consequences of the profusion of images used in the educational process inside and outside the monastery. This research falls within the area of Educational Processes and Language for presenting a proposal of methodological diversity starting from a tradition different from the Western one and little explored by the Brazilianacademy. Moreover, the linguistic and cultural difference itself points to new approaches tothe educational process that seek to broaden our horizon of understanding from ahermeneutical approach. The research is divided into three parts: a field survey between theyears 2014 and 2015 covering Indian archaeological sites, personal experiences in a Nepalese monastery and bibliographic research on the subject. The structure of the work first presents a history of Buddhist education, followed by a possible approach to the development of its iconography and, finally, comparison of classical texts with contemporary academi approaches. The ethnographic experience serves as a backdrop and permeates the whole text.